2019
DOI: 10.1016/j.chemosphere.2018.12.177
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to a pollutant mixture at low doses led to tissue-specific metabolic alterations in male mice fed standard and high-fat high-sucrose diet

Abstract: Excessive consumption of industrialized food and beverages is a major etiologic factor in the epidemics of obesity and associated metabolic diseases because these products are rich in fat and sugar. In addition, they contain food contact materials and environmental pollutants identified as metabolism disrupting chemicals. To evaluate the metabolic impact of these dietary threats (individually or combined), we used a male mouse model of chronic exposure to a mixture of low-dose archetypal food-contaminating che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…Importantly, we observed that the response to the mixture of pollutants was highly tissue-dependent extending our previous data [26,50]. While we did not identify estrogenomimetic activities of the pollutant mixture in the liver, the situation was clearly distinct in SAT.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Importantly, we observed that the response to the mixture of pollutants was highly tissue-dependent extending our previous data [26,50]. While we did not identify estrogenomimetic activities of the pollutant mixture in the liver, the situation was clearly distinct in SAT.…”
Section: Discussionsupporting
confidence: 75%
“…We expected these genes to exhibit changes in mRNA levels in response to chronic exposure to a mixture of archetypal endocrine disruptors previously identified as bearing some estrogeno-mimetic activities as well as metabolic disrupting effects [25,27,50]. Specifically, the protocol used herein was adapted from the published previous model [25,26] except that female mice were not exposed to the [25,27,50], the mixture did not impact body weight. No changes were observed in glucose tolerance or insulin resistance in the mice exposed compared to those not exposed to the pollutant mixture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of the current study was to address the implication of glucocorticoid signaling in mediating the effects of the pollutants in female mice. We also looked for sexual dimorphism benefiting from male samples taken in a previous study (Naville et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, epidemiological data from humans and experimental data from rodents indicate that exposure to certain EDs, the so-called metabolism disrupting chemicals (MDCs), may predispose patients to different components of metabolic syndrome, T2D, and NAFLD (for reviews, see [15][16][17][18][19][20]). The main targets for MDCs are liver and adipose tissue, where they can provoke, e.g., adipogenesis and fat accumulation [21], insulin resistance [22], and changes in cholesterol and bile acid metabolism [18][19][20]. MDCs have also been shown to regulate nutrient ingestion and metabolism by altering the composition of gut microbiota and intestinal transport.…”
Section: Introductionmentioning
confidence: 99%